Office of the special project facilitator lessons learned Sri Lanka integrated road investment program. (Metro Manila, Philippines Asian Development Bank, 2020)
This publication discusses issues and resolutions relating to an integrated road investment project in Sri Lanka as one of the Office of the Special Project Facilitator (OSPF) Lessons Learned series of case studies on ADB complaint management experience.It presents the issues, challenges, and solutions that OSPF identified from its experience responding to the concerns of affected households and people in the course of the project implementation. The OSPF case study series aims to support ADB operations departments, government and private sector partners, and other stakeholders by documenting grievance redress management experiences and identifying important lessons and good practices on problem solving that are useful for future projects.
Keywords: Transportation -- Economic aspects; Roads and highways; Electronic books